FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR: PROFESIONALISME, KOMPETENSI AUDITOR DAN INTEGRITAS AUDITOR - Rahadian Amrullah (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of professionalism, competence, and integrity on auditor performance through an in-depth literature review. The analysis synthesizes findings from national and international journal articles that discuss these three dimensions as key determinants of audit quality. Results indicate that professionalism fosters compliance with auditing standards, competence enhances technical accuracy and analytical ability, and integrity ensures objectivity and ethical behavior in decision-making. Collectively, these elements shape the credibility and effectiveness of auditors in fulfilling their responsibilities. The novelty of this paper lies in integrating the three variables into a single conceptual framework that can guide future empirical studies. This review emphasizes that improving auditor performance requires continuous professional education, ethical reinforcement, and adaptation to digital auditing developments.